Extracorporeal Cardiopulmonary Resuscitation (ECPR) in the Prehospital Setting: An Illustrative Case of ECPR Performed in the Louvre Museum. (4th May 2017) - Lamhaut, Lionel; Hutin, Alice; Deutsch, Juliette; Raphalen, Jean-Herlé; Jouffroy, Romain; Orsini, Jean-Pierre; Baud, Frédéric; Carli, Pierre
Abstract: Introduction: Extracorporeal Cardiopulmonary Resuscitation (ECPR) is now considered for the treatment of refractory cardiac arrest.Case report: In an urban city like Paris, extraction times of in-hospital ECPR can be long for patients presenting with refractory cardiac arrest. Using the medicalized prehospital system, we developed a possible early prehospital ECPR implementation. This case report is an example of ECPR prehospital implementation in the Louvre Museum.Conclusion: Patients eligible for ECPR must be selected according to strict criteria. Further research is necessary to compare prehospital and in-hospital implementation.